Design of a Two-Wheel Tractor Workshop Using Systematic Layout Planning (SLP) and Activity Relationship Chart (ARC) - Gigieh Henggar Jaya; Tiara Ramadhani; Nadia Rakeisya Maulida; Nabilah Nurbayti; Tantri Adelia Putri; Sinta Dwi Pratiwi; Purwoko Hari Kuncoro; Setya Permana Sutisna (Malikussaleh Journal of Mechanical Science and Technology, 2026)
The increasing utilization of two-wheel tractors in agricultural mechanization necessitates the availability of adequate maintenance and repair facilities. However, a major issue frequently encountered is the absence of workshops with effective layouts and installations, which results in inefficient workflows and heightened occupational safety risks. This study aims to design the layout and installation of a two-wheel tractor workshop that emphasizes spatial efficiency, workflow organization, ergonomics, and occupational health and safety (OHS). The research method employed is descriptive quantitative, utilizing the Systematic Layout Planning (SLP) approach and the Activity Relationship Chart (ARC). The proposed design consists of a 120 m² workshop layout divided into ten main zones, applying a one-way straight-line workflow pattern. Comparative analysis demonstrates that the proposed layout significantly improves operational efficiency, as indicated by a 42.8% reduction in unit transfer distance (from 28 m to 16 m), a decrease in spare part retrieval time from 5 minutes to 2 minutes, and an increase in effective workspace utilization from 62% to 85%. The design also fully integrates OHS aspects into the spatial arrangement and employs part catalog analysis to optimize the placement of work equipment. In conclusion, the application of SLP and ARC approaches successfully produces a workshop facility design that is more efficient, organized, and safe, making it suitable for both operational needs and educational practice in agricultural machinery and equipment.